The scientific questions and technological opportunities of flash sintering: From a case study of ZnO to other ceramics. (15th March 2018) - Luo, Jian
Abstract: This viewpoint article critically assesses several scientific and technological questions regarding flash sintering: (1) How does a flash start? (2) What are the possible mechanisms of rapid densifications? (3) What are the electric field/current/potential effects? (4) Can we drastically reduce the flash temperature (or even start a flash at room temperature)? (5) Can we control the microstructures ( e . g ., fabricate dense nanocrystalline ceramics) by manipulating the electric field/current profile? ZnO is discussed as an examplar but other materials are also critically reviewed. New results of both ZnO and Y2 O3 -statabilized ZrO2 are presented. Open scientific questions and new technological opportunities are discussed. Graphical abstract: Image 1